PENGARUH MOTIVASI, KEPEMIMPINAN YANG MELAYANI (SERVENT LEADERSHIP) DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS KOPERASI, UKM DAN PERDAGANGAN KOTA PEMATANGSIANTAR - STEVEN, ORLANDO (JURNAL ILMIAH KOHESI, 2024)
This study aims to analyze the influence of motivation, servant leadership, and organizational climate on employee performance at the Pematangsiantar City Cooperatives, Small and Medium Enterprises, and Trade Office. There are three main questions that are the focus of this study: (1) How does motivation affect employee performance? (2) How does serving leadership affect employee performance? (3) How does the organizational climate affect employee performance?. This research is expected to make a theoretical contribution to the development of Human Resource Management (HRM) by explaining the relationship between these variables, as well as providing practical benefits for related agencies in formulating policies and programs to improve employee performance. The results of this study are also expected to be a reference for future research that wants to use different tools or variables in the same or similar context. In addition, this study aims to improve researchers' knowledge and understanding of issues related to human resource management, especially those related to the influence of work motivation, leadership, and organizational climate on employee performance.